The PAVE study (Physical Activity Virtual Education): development of reusable learning objects (RLOs) to enhance nursing students' knowledge and understanding of physical activity - Blake, Holly; Wharrad, Heather (University of Nottingham. Centre for Integrative Learning, 2010)
The aim of this project was to design, build and test two sustainable reusable learning objects (RLOs) for physical activity (PA) and provide opportunities to assess changes in knowledge and self-reported behaviour following exposure. The RLOs developed for this project encourage self-directed learning and help to foster transformational learning and facilitate critical reflection. Specifically, this means that students will be able to work through the content independently and engage with the RLO at a time and place convenient to them – an important factor in nursing since our students spend a significant proportion of time outside of the university setting. This project supports the integration of new technologies into the traditional learning environment for health promotion. The RLOs will be used as an interactive medium to promote the understanding of physical activity as both a key public health issue and one that they need to address both professionally (through their role as a nurse) and personally (through applying what they learn to their own behaviour). Additionally, the project will support critical reflection on students’ learning, since there will be opportunities to assess students’ knowledge and behaviour change before and after they have engaged with the RLOs.